How current law and policy supports providers of NHS healthcare in England to respond to patient harm: A scoping review protocol. - Naomi Assame; Susan Greenhalgh; John Tingle; Julie Wright; Gillian Yeowell (PLoS ONE)
Introduction Harm arising from National Health Service (NHS) healthcare results in significant human cost for the patient, those who care for them, and the medical staff involved. Furthermore, patient harm results in substantial financial costs to the public purse. Improving how NHS providers in England respond to patient harm could reduce the number of claims for clinical negligence brought against NHS. Doing so will ensure those affected receive the justice they deserve and protect the public purse. Law and policy are key to supporting providers of NHS healthcare to respond to patient harm but are not necessarily understood and therefore can be challenging to apply to practice. Research exploring how law and policy supports this understanding is limited. The purpose of this scoping review is to address this knowledge gap and improve understanding by critically evaluating how law and policy supports providers of NHS healthcare in England to respond to patient harm. Methods and analysis The review will use the methodological framework proposed by Arskey and O'Malley, Levac et al and the Joanna Briggs Institute. Search strategies will be developed using selected key words and index terms. MEDLINE, CINAHL, and Westlaw and reference lists of relevant publications will be searched to identify relevant grey literature. Two reviewers will independently assess the extracted data against the eligibility criteria. All studies identified will be charted and the results presented as a narrative synthesis.